1982
DOI: 10.21273/jashs.107.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Flowering of Vigorous Apple Trees as Affected by Summer or Dormant Pruning1

Abstract: Summer pruning of ‘Starking Delicious’, ‘Golden Delicious’, or ‘Stayman’ apple (Malus domestica Borkh.) trees in mid-August (about 14 weeks after full bloom) did not suppress shoot growth the following year, as compared to similar pruning prior to budbreak in early April. ‘Stayman’ trees pruned in June had more regrowth than those pruned in August. A 1% naphthaleneacetic acid (NAA) solution applied to the summer pruning cut prevented regrowth. The increase in trunk and branch circumference was reduced by Augus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
19
3

Year Published

1982
1982
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 3 publications
6
19
3
Order By: Relevance
“…In contrast, summer pruning consis tently reduced trunk circumference increase of 'Cortland' and of 'Red Prince' the last 2 years. This is in general agreement with Marini and Barden (13,15) and Alderman and Auchter (1). Taylor and Ferree (19) reported that summer pruning most effectively reduced growth of the stem base and roots of pruned trees.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In contrast, summer pruning consis tently reduced trunk circumference increase of 'Cortland' and of 'Red Prince' the last 2 years. This is in general agreement with Marini and Barden (13,15) and Alderman and Auchter (1). Taylor and Ferree (19) reported that summer pruning most effectively reduced growth of the stem base and roots of pruned trees.…”
Section: Discussionsupporting
confidence: 91%
“…Summer pruning failed to restrict terminal growth on 'Red Prince' and increased it on 'Cortland' (Tables 1 and 2). These findings and those of others (13,15,17) are in conflict with the suggestion that a major benefit of summer pruning is supression of terminal growth (22). In contrast, summer pruning consis tently reduced trunk circumference increase of 'Cortland' and of 'Red Prince' the last 2 years.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…The reserves are utilized in spring growth until new shoots become photosynthetically self-sufficient (16). We previously found that radial growth of trunks and scaffold limbs was suppressed by August pruning of mature 'Delicious' and 'Golden Delicious' trees the year of treatment (14). Summer pruning in this study significantly suppressed trunk growth the year of treatment, but not the following year.…”
Section: Discussionsupporting
confidence: 41%
“…In some experiments, summer pruning suppressed shoot growth more the season following treatment than did comparable dor mant pruning (1,2). In other experiments, shoot growth was not suppressed (22) or was stimulated (14) the year following summer pruning in comparison with a similar type of dormant pruning or a nonpruned control (11). At the end of the season, dry weights of roots and stems of young summer-pruned apple trees were less than those of unpruned controls (2 0 ), but data were not presented for growth the year following treatment.…”
mentioning
confidence: 87%